Case Report: A Case of Epileptic Disorder Associated With a Novel CNTN2 Frameshift Variant in Homozygosity due to Maternal Uniparental Disomy - Chen, Wenjie; Chen, Fei; Shen, Yiping; Yang, Zhixian; Qin, Jiong (Frontiers in Genetics, 2021)
Background: Contactin 2, encoded by CNTN2, is a neural-specific glycoprotein and plays important roles in neurodevelopment. A deleterious homozygous variant in the CNTN2 gene was previously reported to cause autosomal recessive cortical myoclonic tremor and epilepsy. Since then, there has been no further report confirming the association of CNTN2 and epilepsy. Here, we reported one new case, who was presented with epilepsy, carrying a novel homozygous variant in CNTN2. The clinical and genetic features of the patient were reviewed. Case Presentation: The male patient presented with preschool age-of-onset neurodevelopmental impairment, focal seizures of temporal origin and responded to valproate. A trio-whole exome sequencing revealed a novel homozygous frameshift variant in CNTN2 (c.2873_c.2874delCT, p.Thr958Thrfs) . The patient’s mother was a heterozygous carrier while his father was wild-type, they were both unaffected and non-consanguineous. Further study revealed that maternal UPD unmasked the heterozygous variant in the proband. Conclusions: This case enhanced the gene-disease relationship between CNTN2 and epilepsy, will help to further understanding this emerging disorder.